تأثير الثقافة السياسية على عملية التحول الديمقراطي في الجزائر - بوكعباش نوال (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يمكن تلخيص موضوع المقال في نقاط محددة، تم التطرق فيها إلى التأثير الذي تحتله الثقافة السياسية في تفعيل عملية التحول الديمقراطي في الجزائر، وبرز تحليل هذا التأثير من خلال دراسة أهمية التنشئة في الثقافة السياسية والعلاقة الوطيدة بينهما، مع ذكر أهم أنواع الثقافة السياسية التي استند عليها العديد من المفكرين السياسيين في تصنيفها، بالإضافة إلى محاولة إبراز دور الثقافة السياسية في تأطير العملية الانتخابية التنافسية، مع ذكر أهم مصادر تكوين الثقافة السياسية في الجزائر وأثرها على الثقافة الديمقراطية في المشهد السياسي، وتم تناول أهم المرتكزات التي تقوم عليها الثقافة السياسية، وعلاقة الثقافة السياسية بالمشاركة السياسية، و التي تعد من مؤشرات الحكم الراشد، وما يلاحظ على عملية المشاركة السياسية في الجزائر ارتفاع نسبتها في الانتخابات الرئاسية وتقل في الانتخابات المحلية والتشريعية. The topic of this article can be summarized in specific points, which were addressed in the analysis, It stands out by the impact that political culture occupies in the effectiveness of the democratization process, with mentioning the most important types of political culture on which many political thinkers based them classification. In addition, trying to highlight the role of political culture in framing the competitive electoral process, with mentioning the most important sources of political culture formation in Algeria and its impact on the democratic culture in the political scene. The most important pillars on which political culture is based, and the relationship of political culture to political participation, which is one of the indicators of good governance, were addressed. What is noticed on the process of political participation in Algeria is a high percentage in the presidential elections and a decrease in the local and legislative elections.